The Practice of Responsible Investment Principles in Larger-Scale Agricultural Investments : Implications for Corporate Performance and Impact on Local Communities - World Bank (Washington, DC, 2014)
This report presents findings from a field-based survey on the conduct of agricultural operations at 39 large-scale, mature agribusiness investments in sub-Saharan Africa and Southeast Asia. The objective of the report is to provide first-hand, practical knowledge of the approach, behavior, and experience of these investments, their relationships with surrounding communities and the consequent positive and/or negative outcomes for these communities, host countries, other stakeholders, and the investors themselves. More than 550 community stakeholders were interviewed about the impacts the investments had on those they represented. These impressions and ideas of local communities enriched this study and provided unique insights into what factors are at play, and their impact on those most directly affected by outside investments. The lessons learned and good practices identified are intended to inform the work of government bodies, investors, non-governmental organizations, development agencies, and other institutions that promote responsible investment in agriculture.